As políticas sociais de reconhecimento como elemento de redução das desigualdades sociais - Alex Pizzio (Ciências Sociais Unisinos)
This study addresses issues relating to social inequalities and social recognition. According to some authors, this last category has taken character of urgency given the supposed link between recognition and identity, where the identity means something like the understanding of who we are, of our essential characteristics as human beings. It is assumed that the nonrecognition or the wrong recognition may cause damage and can configure itself as a form of oppression, that imprisons someone in a way to be false, distorted and reductive. The aim of this discussion, is to show that the policies of recognition set in a field of possibilities, which is an area of formulation and implementation of collective projects, aims at conquering and expanding the social rights characteristic of citizenship, reflected in the decrease of social inequalities in democratic regimes.